The Effect of Material And Roof Shape On Thermal Comfort In Residential Buildings - Ginting, Sola Gratia; Novrial (International Journal of Architecture and Urbanism, 2024)
Indonesia is a country that has a tropical climate with humidity high air which can reach 80%, as well as relatively high air temperature (can reach 35°C). While the comfortable air temperature ranges between 22.5°C - 29°C with humidity air ranges from 20% - 50%). Therefore, it is necessary to create comfort thermal space in the space where people perform movement and activity. One of the things the most important thing is the use of the roof. The roof has an influence on temperature and comfort in space, especially in terms of material use and shape selection roof of the building. The use of roof forms with different materials certainly will creates a different effect on buildings.